1986
DOI: 10.1016/s0735-1097(86)80201-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of regional myocardial function by cine computed tomography: Pharmacologic changes in wall thickness

Abstract: To determine the capability of high speed computed transmission tomography to quantitate regional wall thickening dynamics over a wide range of physiologic states, left ventricular wall thickening was studied in nine anesthetized mongrel dogs in the control state and during separate infusions of dobutamine (10 micrograms/kg per min) and phenylephrine (25 micrograms/kg per min). After an intravenous bolus of contrast medium the heart was imaged from base to apex with serial transverse images in eight short-axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 37 publications
1
5
0
2
Order By: Relevance
“…In an experimental study, despite a fivefold increase in RMBF, systolic wall thickening increased by ϳ100% (26). In clinical studies, normal subjects demonstrated an increase in wall thickening with dobutamine of 70% to 120%, using echocardiography, magnetic resonance, and computed tomography (24,27,28). In contrast, our data demonstrate a five-to six-fold increase in sSR, with a similar increase in RMBF (Fig.…”
Section: Discussionsupporting
confidence: 44%
“…In an experimental study, despite a fivefold increase in RMBF, systolic wall thickening increased by ϳ100% (26). In clinical studies, normal subjects demonstrated an increase in wall thickening with dobutamine of 70% to 120%, using echocardiography, magnetic resonance, and computed tomography (24,27,28). In contrast, our data demonstrate a five-to six-fold increase in sSR, with a similar increase in RMBF (Fig.…”
Section: Discussionsupporting
confidence: 44%
“…In a previous study of normal controls by other methods, the %WT was smallest for the septum and greater for the lateral and inferior walls. [22][23][24][25][26][27][28][29] In previous ECGgradual decrease from ES to ED. Heterogeneous wall gated PET studies, the percent of count increase (corresponding to our %WT) was lowest (32.9+ 7.2%) for the septum and highest (72.8+26.5%) for the lateral wall.…”
Section: Segments Of Left Ventricular Wallmentioning
confidence: 99%
“…Computertomographische Screening-Verfahren auf arteriosklerotische Gefäßveränderun-gen stützen sich auf den Nachweis von Gefäßverkalkungen [6]. Beispielsweise soll die Quantifizierung der koronaren Kalkmasse mittels Elektronenstrahlcomputertomographie mit dem Schwergrad einer koronaren Herzkrankheit korrelieren [1,15,23]. Solche Verfahren sind nach unserer Auffassung kritisch zu betrachten, da Gefäßverkal-kungen nicht nur arteriosklerotischer Genese sein können und somit eine nachgewiesene Koronarverkalkung unter anderem auch der atypisch lokalisierten Manifestation einer disseminierten Mediasklerose Mönckeberg entsprechen kann.…”
Section: Klinische Symptomatikunclassified